Rehabilitation of a Completely Edentulous Patient with Nonreducible Bilateral Anterior Dislocation of the Temporomandibular Joint: A Prosthodontic Challenge—Clinical Report. Issue 5 (27th July 2015) - Momani, Moath; Abdallah, Mohamed‐Nur; Al‐Sebaie, Derar; Tamimi, Faleh
Abstract: Nonreduced bilateral anterior dislocation of the temporomandibular joint (TMJ) is an extremely rare condition, and its prosthodontic rehabilitation is a clinical challenge, especially in patients who refuse to or cannot undergo surgery. There are no previous clinical reports of successful or standardized prosthetic rehabilitation approaches for patients with this condition. This clinical report describes the successful prosthodontic management of an edentulous patient with nonreduced bilateral anterior dislocation of the TMJ.